Selective inhibition of brain endothelial Rho-kinase-2 provides optimal protection of an in vitro blood-brain barrier from tissue-type plasminogen activator and plasmin. - Be'eri Niego; Natasha Lee; Pia Larsson; T Michael De Silva; Amanda E-Ling Au; Fiona McCutcheon; Robert L Medcalf (PLoS ONE)
Rho-kinase (ROCK) inhibition, broadly utilised in cardiovascular disease, may protect the blood-brain barrier (BBB) during thrombolysis from rt-PA-induced damage. While the use of nonselective ROCK inhibitors like fasudil together with rt-PA may be hindered by possible hypotensive side-effects and inadequate capacity to block detrimental rt-PA activity in brain endothelial cells (BECs), selective ROCK-2 inhibition may overcome these limitations. Here, we examined ROCK-2 expression in major brain cells and compared the ability of fasudil and KD025, a selective ROCK-2 inhibitor, to attenuate rt-PA-induced BBB impairment in an in vitro human model. ROCK-2 was highly expressed relative to ROCK-1 in all human and mouse brain cell types and particularly enriched in rodent brain endothelial cells and astrocytes compared to neurons. KD025 was more potent than fasudil in attenuation of rt-PA- and plasminogen-induced BBB permeation under normoxia, but especially under stroke-like conditions. Importantly, only KD025, but not fasudil, was able to block rt-PA-dependent permeability increases, morphology changes and tight junction degradation in isolated BECs. Selective ROCK-2 inhibition further diminished rt-PA-triggered myosin phosphorylation, shape alterations and matrix metalloprotease activation in astrocytes. These findings highlight ROCK-2 as the key isoform driving BBB impairment and brain endothelial damage by rt-PA and the potential of KD025 to optimally protect the BBB during thrombolysis.